A Review of Functions of Speculative Thinking - Huang, Lun; Xie, Yibo; Chen, Xiaolin (Frontiers in Psychology, 2021)
Speculative thinking refers to thinking about past or future possibilities; it includes counterfactual thinking, prefactual thinking, and other types. In this narrative review, we discuss the traditional function of speculative thinking in improving future performance (i.e., the preparatory function). We also explore several non-preparatory functions of speculative thinking that have not been widely covered, namely the functions of conveying information and of supporting lying. In addition, we address temporal asymmetry; one perspective focuses on psychological distance in speculative thinking about the past and future, while another focuses on temporal asymmetry and reality/hypothetical differences in the preparatory function of speculative thinking. Overall, this review suggests that a broader functional theory is needed to address non-preparatory functions and the traditional preparatory function. Such a theory should cover all speculative thinking about the past and future rather than simply counterfactual thinking.